Asymmetric dimethylarginine (ADMA), 4-OH-nonenal and Vitamin E levels in chronic schizophrenic patients - Telo, Seida; Gurok, Mehmet Gurkan (Elsevier Ireland Ltd, 2016)
[Abstract Not Available]
Keywords: Oxidative Stress; Nitric-Oxide; Lipid-Peroxidation; Atypical Antipsychotics; 1St-Episode Psychosis; Antioxidant Defense; Bipolar Disorder; Plasma; Brain; Inflammation